Research on the Netflix Stock Price based on Linear regression Models - Xie Xiangming (SHS Web of Conferences, 2024)
This article uses a linear regression model to predict Netflix’s stock from 2018 to 2022, and divides the data set into pre- and post-epidemic analysis. The before-and-after analysis aims to explore the impact of COVID-19 on Netflix stock price. By collecting and collating Netflix’s historical stock price data, financial indicators, and other relevant information, a linear regression model was constructed. Through model training and verification, the prediction results of future stock prices are obtained, and a comparative analysis before and after the epidemic is carried out. The research results have important reference value for investors, analysts and decision makers in formulating investment strategies and risk management.